Study of patient profile of children with poor/delayed speech in a tertiary care centre in Western Uttar Pradesh, India - Sen, Moumita; Chatterji, Probal (Asian Journal of Medical Sciences, 2021)
Background: Humans convey their emotions and information to one another through language. Delayed or poor speech can have a profound effect on the social and professional life of a person. Aim and Objectives: A study of children with poor/delayed speech in a tertiary care centre in western U.P. Objectives were as follows • To study the risk factors for congenital hearing loss in children with poor/no speech. • To screen them regarding their hearing status. • To analyze results in detail and compare with available literature. Materials and Methods: A hospital based prospective observational study was done from Jan - Dec 2019. One-hundred fifteen children were identified. Hearing screening was done in all of them by OAE testing followed by tympanometry and BERA wherever applicable. Results: Out of 115 children, 9 (7.8%) had normal hearing, 9 (7.8%) had central cause of deafness and 97 (84.4%) had congenital SNHL. 64% of subjects were male (p value- <0.001). 79% of them had an association with some risk factor during birth (p value- <0.001). 40.8% of them were first order in birth with a typical age group presentation of 2-3 yrs. 60.1% of the study population with SNHL had history of normal delivery at home. Conclusion: Improvement in the quality of antenatal care, obstetric services and postnatal care will reduce the number of cases of congenital sensorineural deafness significantly by reducing the number of high-risk babies. Moreover, the introduction of practice of universal hearing screening of newborns will help in identifying them early for proper rehabilitation.